First report of molecular detection of chicken astrovirus (CAstV) in chicks affected with enteric disease in Ecuador through a fast RT-qPCR assay based on SYBR® Green - Silvana Santander-Parra; Claudete Astolfi-Ferreira; Anthony Loor-Giler; Nikolaos C. Kyriakidis; Antonio J. Piantino Ferreira; Luis Núñez (BMC Veterinary Research)
Abstract Background Chicken meat production has expanded considerably on a global scale due to its ease of production compared to other species. As a result, the prevalence of avian viruses has grown. Chicken astrovirus (CAstV), an RNA virus with roughly 7 kb in length that is disseminated globally and exhibits both horizontal and vertical transmission, is one of the most important enteric pathogenic avian viruses. CAstV and some enteric viruses’ infections causes significant economic losses because they are associated with high mortality in chickens. CAstV cause a variety of pathologic changes such as runting and stunning syndrome, nephritis, and white chick syndrome, making early detection critical. For this purpose, the objective of this study was to determine the presence of CAstV in chickens affected with enteric disease through a fast RT-qPCR assay based on SYBR® Green. For this, 120 samples of jejunum from seven-day-old chicks that succumbed to enteric disease characterized by pronounced lethargy, apathy, diarrhea and cloacal pasting were subjected to investigation. Results At necropsy, the intestines of all chicks appear pale and filled with yellow or green liquid content, thin wall and presence of gas; at the jejunum it was evidenced the presence of remanent yolk sac. The liver, kidneys, spleen did not show any alteration. CAstV RNA was detected and quantified in 85 samples, revealing significant levels (9.6 × 10^6) of CAstV gene copies. This indicates the presence of the virus in Ecuadorian chicks from a few days of age, suggesting vertical transmission and potential sources for the virus’s dissemination. The phylogenetic analysis clustered all Ecuadorian sequences in one group related to sequences from India and Brazil. The comparison identity of NT sequences in part of Orf 1b gene showed 83.27 − 93.5% with other sequences of CAstV from India and Brazil. Additionally, the LoD and LoQ were determined in 101 gene viral copies. The standard curve showed an efficiency of 97.3% and a melting curve showed a single peak without any alterations and a melting temperature of 77.5 °C. The assay was specific for amplification of the CAstV genome and no amplification was shown from other viral genomes (aMPV, NDV, IBV, AReV, ARoV, ANV) or from the negative controls. Conclusions Presents, for the first time, the detection of CAstV in chicks suffering from enteric disease in Ecuador. It also demonstrates that the assay developed herein is an effective tool for the early detection and quantification of CAstV in diseased chickens, while being a reliable, specific, cost-effective, and rapid diagnostic method.